Improvement of contact resistivity of titanium silicide on P-doped epitaxial Si using a Se interlayer. (27th October 2020) - Park, Seran; Choi, Jeong-Min; Shin, Hyunsu; Ko, Eunjung; Ko, Dae-Hong
Abstract: We propose a method to reduce the contact resistivity of titanium silicide (TiSi2 ) on phosphorus-doped epitaxial silicon by introducing a thin Se layer at the Ti/Si interface. The Se interlayer delays transition from the C49 to the C54 phase and changes the dominant diffusing species of TiSi2 formation from Si to Ti. In addition, the Se interlayer worsens the interface roughness between TiSi2 /Si. The contact resistivity of the sample with the Se interlayer improves by one order of magnitude, which is significant. This improvement is attributed to the suppressed diffusion of P and low Schottky barrier height.